Assessing governance challenges of local biodiversity and ecosystem services: Barriers identified by the expert community. (February 2020) - Shih, Wan-Yu; Mabon, Leslie; Puppim de Oliveira, Jose A.
Highlights: Expert survey into governance challenges for biodiversity & ecosystem services. Survey covers 45 cities in 25 countries, covering Global North & South contexts. Concerns over budget; and limited BES knowledge in development & planning sectors. Non-governmental experts more concerned about policy change with new administration. Unsustainable but meaningful cultural activity may run up against BES conservation. Abstract: This paper assesses barriers to local biodiversity and ecosystem (BES) governance within cities, drawing on findings from an international expert survey encompassing 45 cities in 25 countries. BES is recognised as a key foundation for sustainable cities, yet current literature indicates that more clarity is needed on the factors which may undermine BES initiatives. Survey findings show broad agreement that officials in development sectors have inadequate BES knowledge, budgets for BES are insufficient, and planners in the locality lack knowledge about BES. Respondents not working for local governments were more likely to see policy change with administrations, budget limitations, and lack of expertise as barriers. Respondents for cities in less-developed countries agreed significantly more that there were harmful cultural activities, and were more concerned that inadequate consideration from governments at different scales and poor internal communication were barriers. Based on the findings, we suggest (a) a need to evaluate the effectiveness of collaboration both within government and between sectors; (b) the importance of building capacity within local government staff, both in techno-scientific knowledge and in engaging the policy landscape with this knowledge; and (c) the importance of further considering how BES conservation may relate to culturally meaningful practices.